The Evaluation of the Utilization of Guava Leaf Plant as Medicine Traditional Antidiaries in Kelurahan Tamalanrea Jaya, Makassar City - Murniati Murniati; Alfreds Roosevelt; Nur Hayati (Politeknik Sandi Karsa, 2021)
Guava plants, especially the leaves, have a higher effectiveness than some other plants used to stop diarrhea. Diarrhea is defined as a disease symptom characterized by changes in the shape and consistency of loose to liquid stools and an increase in the frequency of bowel movements more than usual, which is more than 3 times per day accompanied by vomiting or bloody stools. The aim of the study was to evaluate the use of guava leaf (Psidium guajava L) as a traditional anti-diarrhea medicine in Tamalanreya Jaya Village, Makassar City. The research method used is a descriptive survey. Sampling in this study by purposive sampling technique. The population in the study was the entire community of RW 001, Tamalanrea Jaya Village, which amounted to six RTs and the sample was RT 004 with 50 respondents. The results showed that the evaluation of the use of guava leaves as a traditional antidiarrheal medicine was included in the fairly good category, namely (70 ,0%). And based on this research, it can also be seen that guava leaf plants are commonly used by the community to treat anti-diarrhea.